2008
DOI: 10.1111/j.1745-6592.2008.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Removal Rates in a 15‐Year‐Old Permeable Reactive Barrier Treating Septic System Nitrate

Abstract: Permeable reactive barriers (PRBs) have gained popularity in recent years as a low-cost method for ground water remediation. However, their cost advantage usually requires that these barriers remain maintenance free for a number of years after installation. In this study, sediment cores were retrieved from a pilot-scale PRB consisting of a sand and wood particle (sawdust) mixture that has been in continuous operation for 15 years treating nitrate from a septic system plume in southern Ontario (Long Point site)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(72 citation statements)
references
References 37 publications
5
65
0
1
Order By: Relevance
“…Since Robertson et al (2008) presents the only decadal study on denitrification walls, long-term studies of denitrification wall performance remain lacking. More information on sustainability is needed including bioreactors utilizing different C media and bioreactors installed in different climates, soils, and groundwater systems.…”
Section: Sustainability Of Denitrification Wallsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Robertson et al (2008) presents the only decadal study on denitrification walls, long-term studies of denitrification wall performance remain lacking. More information on sustainability is needed including bioreactors utilizing different C media and bioreactors installed in different climates, soils, and groundwater systems.…”
Section: Sustainability Of Denitrification Wallsmentioning
confidence: 99%
“…To date, Robertson et al (2008) presents the only decadal study of the performance of denitrification walls. This study revisited the wall installed downgradient of a septic tank in Canada after 15 years of use (Robertson and Cherry, 1995).…”
Section: Sustainability Of Denitrification Wallsmentioning
confidence: 99%
See 1 more Smart Citation
“…These reactive materials were selected as substrates for the growth of denitrifying bacteria in a field-scale barrier system (Herbert and Björnström, 2009); other denitrification studies have shown that sawdust is a suitable substrate (e.g. Robertson et al, 2008;Schipper et al, 2004), providing a long-term carbon source for the growth of heterotrophic denitrifying bacteria. The sewage sludge is included because it is a source of denitrifying bacteria and allows for the rapid establishment of a denitrifying community in the columns.…”
Section: Column Experimentsmentioning
confidence: 99%
“…chlorinated solvents, nitrate), reactive materials generally consist of electron donor sources such as zerovalent iron (Fe 0 ) or organic carbon (Blowes et al, 2000). Organic substrates have been chosen in a variety of cases (Benner et al, 2002;Blowes et al, 1994;Robertson et al, 2008;Schipper et al, 2004) where carbon sources are required for heterotrophic microbial reduction of groundwater constituents (e.g. dissimilatory sulfate reduction, denitrification).…”
Section: Introductionmentioning
confidence: 99%